The Effectiveness of Career Adaptability Training For Final Year Students - Suryadi Tandiayuk; Elvita Bellani; Angie Fabiola Susanto3; Farid Firmansyah (Pusat Penerbitan dan Publikasi Ilmiah, Fakultas Ekonomi dan Bisnis, Universitas Muslim Indonesia, 2022)
Career transition from student to worker is an important phase that determines individual success in their work. However, in reality, students do not prepare their careers well so they are less able to adapt to their career choices. This study aims to determine the effectiveness of career adaptability training for final year students. This research method is an experimental model with a within group pre and post test design with a total sample of 18 people. The results of the Wilcoxon test showed p value = 0.003, so it can be concluded that there is a difference in the average career adaptability of final year students before and after being given training. Thus, career adaptability training can be an alternative intervention given to final year students in order to adapt to their career choices.